The Variable Sample Size (X)over-bar Chart with Estimated Parameters - Castagliola, Philippe; Zhang, Ying; Costa, Antonio [UNESP]; Maravelakis, Petros (Wiley-Blackwell, 2012)
The VSS X chart, dedicated to the detection of small to moderate mean shifts in the process, has been investigated by several researchers under the assumption of known process parameters. In practice, the process parameters are rarely known and are usually estimated from an in-control Phase I data set. In this paper, we evaluate the (run length) performances of the VSS chart when the process parameters are estimated, we compare them in the case where the process parameters are assumed known and we propose specific optimal control chart parameters taking the number of Phase I samples into account.
Keywords: (X)over-bar chart; adaptative chart; estimated parameter; run length